Nucleoside reverse transcriptase inhibitor‐reducing strategies in HIV treatment: assessing the evidence. Issue 1 (24th July 2017) - Orkin, C; Llibre, JM; Gallien, S; Antinori, A; Behrens, GMN; Carr, A
Abstract : Antiretroviral (ARV) therapy, comprising a backbone of two nucleos(t)ide reverse transcriptase inhibitors (NRTIs) plus another ARV, is the recognized standard of care (SOC), which has helped extend life expectancy in people living with HIV. In a quest to reduce lifelong drug exposure and minimize or avoid the toxicity of NRTIs, "NRTI‐reducing" regimens have been investigated. This descriptive review assessing the results of NRTI‐reducing strategies from the largest randomized trials focuses on virological efficacy, resistance, regimen safety (in terms of bone mineral density, renal function, lipids and central nervous system function) and simplicity. The review considers efficacy across various NRTI‐sparing strategies, for example an integrase strand transfer inhibitor (INSTI) plus a ritonavir‐boosted protease inhibitor (PI/r) or PI/r + lamivudine (3TC), in both naïve and switch regimes. Of 10 key studies in treatment‐naïve adults assessing five NRTI‐reducing strategies, only four studies demonstrated noninferiority vs . SOC [GARDEL, NEAT 001, AIDS Clinical Trials Group 5142 and PROGRESS]. In switch settings, 17 studies (10 randomized) were reviewed that used four strategies, including three studies assessing an INSTI plus a nonnucleoside reverse transcriptase inhibitor . Noninferiority of the NRTI‐reducing arm was shown in six of 10 studies (ATLAS‐M, SALT, DUAL, OLE, LATTE‐2 and SWORD). In general, NRTI‐reducing therapy did not always result in an improvement in short‐ or long‐term adverse events; however, in many cases, these endpoints were not reported. Some of these studies reported higher virological failure rates with more frequent emergence of resistance mutations. None of these NRTI‐reducing strategies has been compared against a single‐pill regimen, including those containing tenofovir alafenamide. Only strategies demonstrating noninferior efficacy, a benefit in safety/tolerability, and a favourable cost‐efficacy ratio, preferably in a single pill, will eventually match the current SOC of triple ARV therapy.